2019
DOI: 10.7567/1347-4065/ab45e3
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress for obtaining the ferroelectric phase in hafnium oxide based films: impact of oxygen and zirconium

Abstract: Different causes for ferroelectric properties in hafnium oxide were discussed during the last decade including various dopants, stress, electrode materials, and surface energy from different grain sizes. Recently, the focus shifted to the impact of oxygen vacancies on the phase formation process. In this progress report, the recent understanding of the influence of oxygen supplied during deposition on the structural phase formation process is reviewed and supplemented with new data for mixed Hf x Zr 1-x O y fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 42 publications
(88 reference statements)
1
76
0
Order By: Relevance
“…During the ALD process for the deposition of HZO film, the TiN bottom electrode was oxidized by a deposition temperature of 250 • C, which was confirmed through the depth profile of the oxygen concentration observed from the D-SIMS results in Figure 5c. This oxidation of the TiN bottom electrode can promote ferroelectric phase formation by increasing the oxygen vacancies at the interface between the TiN electrode and the HZO film [2,8,14,21]. This phenomenon, known as oxygen scavenging, can occur further during the RTA process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the ALD process for the deposition of HZO film, the TiN bottom electrode was oxidized by a deposition temperature of 250 • C, which was confirmed through the depth profile of the oxygen concentration observed from the D-SIMS results in Figure 5c. This oxidation of the TiN bottom electrode can promote ferroelectric phase formation by increasing the oxygen vacancies at the interface between the TiN electrode and the HZO film [2,8,14,21]. This phenomenon, known as oxygen scavenging, can occur further during the RTA process.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that the thickness range of the feasible ferroelectric performance of HZO film can be reduced to 5 nm [4,5]. In this regard, numerous studies have been reported in various fields, such as ferroelectric random-access memory (FRAM), ferroelectric field-effect transistors, synaptic devices, and energy storage applications [6][7][8]. Based on theoretical reports and experimental demonstrations, the non-centrosymmetric orthorhombic phase (o-phase, space group: Pca2 1 ) is now believed to be the reason for the origin of the ferroelectric behavior in these HZO films [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the fluorite-structure ferroelectrics exhibit suitable ferroelectric properties even at the sub-10 nm scale and can be deposited on complicated 3D structures using mature deposition techniques such as atomic layer deposition (ALD). [2][3][4][5][6] Meanwhile, in addition to these advantages that are compatible with complementary metal-oxide-semiconductor (CMOS) technology, the ferroelectricity of fluorite-structure oxides can also be achieved even in low-thermal-budget (400 C or less) processes, unlike perovskite-structure ferroelectrics (600 C or higher). [4] These low-thermal-budget thin-film deposition and subsequent annealing processes facilitate the integration of ferroelectric circuits in the back-end-of-line (BEOL), providing benefits such as increasing the effective memory area and adding more functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Park et al [13] had proposed that the formation of the Pca2 1 phase under certain processing conditions stemmed from a large tensile strain along the c-axis of the tetragonal phase. Schroeder et al [14] reviewed the strong influence of Zr and O contents on the crystallization and phase stabilization in ultrathin films of hafnia-zirconia deposited by atomic layer deposition and other depositions methods along with their impact on polarization and ferroelectric phases. Onaya et al [15] had reported that the HZO stack sandwiched with top and bottom nucleation layers of ZrO 2 exhibited superior ferroelectric polarization and reported correlation with the larger relative ratios of orthorhombic\tetragonal \cubic phases with respect to the monoclinic phase.…”
Section: Introductionmentioning
confidence: 99%